Design and development of a tribometer for the measurement of friction - Muhammad Rusydi Abdul Rahman (2014)
As friction is present various mechanical systems, such as brakes, clutches, bearings, etc., it is important that the full effects of friction is understood. This is so the designer can either eliminate or; design around or with the friction in mind. This is an important aspect as friction can come across as a form of disturbance in the system and may cause a safety issue if unaddressed.